PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL PENEMUAN TERBIMBING PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK LINEAR SATU VARIABEL UNTUK KELAS X SMA/MA - Ardilo Indragita; Sehatta Saragih; Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to develop mathematics learning device that are Lesson Plan (LP) and Students Worksheet (SW) and 2013 curriculum-based with discovery learning model on the equations and inequalities of linear one varible absolute value material. This development research uses 4D development model who developed by Thiagarajan and modified by Endang Mulyatiningsih. The development carried out by the stages: (1) define; (2) design; (3) development; and (4) dessemination that is not implemented due to time and cost limitations. Data collection instrumen in this study were LP and SW validation sheets and student response questionaires. Then, learning device that had been compiled are validated by three validators and revised according to validator’s suggestions. Then, learning device that had been validated are tested in two stages, namely small group trials with the subject of six students of class X.4 SMA Negeri Plus Provinsi Riau and a large group trial with the subject of 20 class X.2 students of SMA Negeri Plus Provinsi Riau. Based on the data analysis results and the discussion it can be concluded that the 2013 curriculum-based mathematics learning device with a discovery learning model on the equations and inequalities of linear one varible absolute value material was considered very valid with the rating average for lesson plans was 3.63 and the rating average for Students Worksheet is 3.62, and meets the practical requirements for use by the students of grade X SHS.Keywords: Mathematics Learning Device, Discovery Learning Models